PENGGUNAAN METODE SILENT WAY DALAM PENGAJARAN BAHASA INGGRIS DI PIAENGLISH COURSE MANADO - PRIHATINI, DYAH AYU (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This study is entitled Silent Way Method Use in Teaching English in PIA English Course Manado. The research question is how the Silent Way Method was used in teaching English in PIA English Course Manado. The aim of the research is to identify and describe the Silent Way Method which was used in teaching English in PIA English Course Manado. In collecting the data, the writer observed a class in PIA for one month. The population is all classes divided into Beginner Class; Power Speaking 1,2,3; Prepatory Practical 1,2; Step Communication 1,2,3,4,5,6; Basic Communication 1,2,3,4,5,6 and Step 1 class was chosen as sample. The data consist of 10 students from different junior high schools in Manado. The data analysis was based on Gateggno’s theory on Silent Way Method. The collected data were identified and analyzed focusing on the aspects of Silent Way Method used in class in PIA English Course including the media. As the result, the teacher in PIA used a syllabus to help in their teaching preparation and in teaching systematically. The teacher’s roles as a lecture, educator and driver of creativity were found in class. Similarly,learners could express their opinion by using their own language, they can also explore words and sentences in English in their own way. As well the learnerin Silent Way Method can be more confident in expressing their questions and statements. The media gave support for the learner in learning English by using Sound – Color – Chart, Teacher’s Silence, Peer Correction, Word Chart and Rod. Keywords : Silent Way Method, English Teaching, Private Course.